2000
DOI: 10.1177/030802260006300904
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy, Gender and Mental Health: An Inclusive Perspective?

Abstract: This article offers an understanding of how the gendered nature of occupational therapy has an impact on relationships between therapist and client, qualified staff and support workers, and occupational therapy managers and workers. It analyses the development of occupational therapy from its early, mainly female and middle-class, origins and explores how the profession has struggled to define its status and role to fit structures determined by the medical profession. The tensions that these pressures have exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…An occupational therapist assists a patient to engage in occupations, in order to ultimately enhance occupational performance or efficiency, and to achieve health through doing. Other authors have also identified the difficulty of enacting occupation‐focused therapy within medically dominated health services (Baum, Berg, Seaton & White, 2002; Bryden & McColl, 2003; Crabtree, 1998a; Jongbloed & Wendland, 2002; Pollard & Walsh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…An occupational therapist assists a patient to engage in occupations, in order to ultimately enhance occupational performance or efficiency, and to achieve health through doing. Other authors have also identified the difficulty of enacting occupation‐focused therapy within medically dominated health services (Baum, Berg, Seaton & White, 2002; Bryden & McColl, 2003; Crabtree, 1998a; Jongbloed & Wendland, 2002; Pollard & Walsh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Perrin () also discusses that occupational therapists are assessing rather than actually working with occupations as therapy and that the reduced use of creative activities as intervention in occupational therapy may be explained by a feeling of embarrassment about being connected with creative activities as such. Another possible explanation may be related to the following statement from Pollard and Walsh ():
Occupational therapy's relationship with medicine has been a one‐sided affair. This feminine profession, based in innovation and solutions to individual problems, in practical and domestic activities, has struggled to accommodate male demands for scientific rigour: thus medicine has still to recognize the value of its work” (p. 426).
In an editorial column, the frequent use of physical agent modalities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Perrin (2001) also discusses that occupational therapists are assessing rather than actually working with occupations as therapy and that the reduced use of creative activities as intervention in occupational therapy may be explained by a feeling of embarrassment about being connected with creative activities as such. Another possible explanation may be related to the following statement from Pollard and Walsh (2000):…”
Section: Introductionmentioning
confidence: 99%
“…The development of leadership skills has been identified as being particularly relevant for a predominantly female professional group, such as occupational therapy (Pollard and Walsh 2000). Acknowledging the existing gender inequalities in the health care system (Sebrant 1999), it could be asked: 'Are occupational therapists sufficiently aware of the impact of gender upon leadership and the use of power in order to ameliorate negative impact and actively promote a female advantage?…”
Section: Introductionmentioning
confidence: 99%